The Locals’ Voices To A Langgher Dhatang Developmental Plan As A Religious Tourism Destination in Madura - Mohammad - Halili; Fatimatus Zahroh (IAIN Ponorogo, 2023)
AbstractLanggher Dhatang symbolizes an Islamic architecture. Some belive that religion should not be commercialized. This article, however, rebuts the given point of views. Therefore, this aims to study three major issues: 1) local perceptions towards the development of Langgher Dhatang as a religious tourism destination, 2) the common-held belief in the interplay between the local tourism destination and economic advantages, and 3) feasible actions to take to make Langgher Dhatang more popular. This employed a quantitave research. Conducting door-to-door interviews with structured questions to collect the data was held. Researchers successfully interviewed 13 local people nearest to the location of Langgher Dhatang as they would be likely to have a direct impact from the scheme. The research shows that the involved participants demonstrated various attitudes when Langgher Dhatang is designed to be a local religious tourism destination. The participants’ responses are everage, ranging from 38.5% (agree), 30.8% (disagree and neither). The responses vary dealing with economic consequences that would possibly bring and their gaps is wide: 69.2% believe that the tourism positively impacts economically, and 15.4% claims that this will have no economic advantages, including 15.4% has no idea with the impact of tourism destination development around them. Some feasible strategies were also proposed. AbstrakLanggher Dhatang menyimbolkan arsitektur agama Islam. Sebagian orang percaya bahwa agama seharusnya tidak boleh dikomersialkan. Akan tetapi, penelitian bertentangan dengan pandangan tersebut. Oleh karena itu, ada tiga hal penting yang menjadi isu dalam penelitian ini: 1) persepsi masyarakat setempat jika Langgher Dhatang dijadikan tujuan wisata religi, 2) pandangan umum terhadap kaitan antara tujuan wisata religi dan keuntungan secara ekonomi, 3) serta strategi yang bisa dilakukan untuk meningkatkan popularitas Langgher Dhatang sehingga pengunjungnya bisa meningkat. Penelitian ini menggunakan pendekatan penelitian kuantitatif. Peneliti melakukan interview dari pintu ke pintu untuk mendapatkan data. Kami berhasil menginterview 13 orang terdekat dengan lokasi Langgher Dhatang. Hal ini disebabkan karena mereka yang terdekat akan terkena dampak secara langsung dari rencana ini. Hasil penelitian ini menujukkan bahwa responden memiliki pandangan yang berbeda terhadap rencana pengembangan Langgher Dhatang sebagai tujuan wisata religi: 38,5% setuju, 30,8% tidak setuju, dan 30,8% netral. Terkait dengan isu ekonomi, responden juga menunjukkan respon yang berbeda. Menariknya, perbedaan persentasenya cukup luas: 69,2% percaya bahwa pengembangan Langgher Dhatang ke arah destinasi wisata memberikan dampak positif terhadap perekonomian mereka, 15,4% justru sebaliknya tidak percaya dampak positif tersebut, dan 14,4% posisi netral. Beberapa strategi yang bisa dilakukan untuk meningkatkan popularitas Langgher Dhatang juga diusulkan.